Lithium secondary battery

By using carbon particle layers with a G-band peak intensity and D-band peak intensity ratio of R of more than R in lithium secondary batteries, the shortage of the fast charging characteristics of lithium precipitation all-solid lithium secondary batteries is solved, and a higher level is achieved The charging capacity and charging and discharging efficiency enhance the safety of the battery.

CN119213596APending Publication Date: 2024-12-27NISSAN MOTOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280096138.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium-precipitation all-solid-state lithium secondary batteries have shortcomings in terms of fast charging characteristics and cannot achieve sufficient fast charging characteristics.

Method used

In a lithium secondary battery, a conductive layer is arranged on the main surface opposite to the solid electrolyte layer. The conductive layer includes a carbon particle layer, and the G-band peak intensity and D-band peak intensity ratio of the carbon particle layer R (IG) Carbon particles with /ID) of 7 or more are used to improve the diffusion of lithium ions and charging efficiency.

Benefits of technology

By using a high-intensity carbon particle layer, lithium secondary batteries can effectively cope with the rate characteristics of fast charging, improve charging capacity and charge and discharge efficiency, and prevent short circuits and improper precipitation of lithium metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213596A_ABST
    Figure CN119213596A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a means capable of exhibiting rate characteristics capable of coping with rapid charging in a lithium-precipitation-type lithium secondary battery. One embodiment of the present invention relates to a lithium secondary battery provided with a power generating element having: a positive electrode in which a positive electrode active material layer containing a positive electrode active material capable of absorbing, storing and releasing lithium ions is disposed on the surface of a positive electrode current collector; a negative electrode having a negative electrode current collector and depositing lithium metal on the negative electrode current collector during charging; and a solid electrolyte layer that is interposed between the positive electrode and the negative electrode and contains a solid electrolyte. Furthermore, the lithium secondary battery is characterized in that: in the negative electrode current collector, a carbon particle layer is disposed on at least a part of a region in which the positive electrode active material layer and the negative electrode current collector face each other on a main surface facing the solid electrolyte layer; the carbon particle layer contains carbon particles in which the intensity ratio R (IG / ID) of the G-band peak intensity (IG) to the D-band peak intensity (ID) measured by Raman scattering spectroscopy is 7 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium secondary battery. Background Art

[0002] In recent years, in order to cope with the global warming effect, it is urgent to reduce carbon dioxide emissions. In the automotive industry, due to the introduction of electric vehicles (EV) and hybrid electric vehicles (HEV), there are high expectations for reducing carbon dioxide emissions. The development of non-aqueous electrolyte secondary batteries such as motor drive secondary batteries, which are the key to their practical application, is booming.

[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to lithium-ion secondary batteries for mobile phones, notebook computers, etc. Therefore, lithium-ion secondary batteries, which have the highest theoretical energy of all batteries in reality, have attracted attention and are currently being developed rapidly.

[0004] Here, currently, the lithium ion secondary battery that is generally used uses a flammable organic electrolyte as an electrolyte. Such liquid lithium ion secondary batteries have stricter safety measures against leakage, short circuit, overcharge, etc. than other batteries.

[0005] Therefore, in recent years, the research and development of all-solid-state lithium secondary batteries using oxide-based and sulfide-based solid electrolytes for electrolytes is booming. Solid electrolytes are materials that use ion conductors that can conduct ions in solids as the main body. Therefore, in all-solid-state lithium secondary batteries, various problems caused by flammable organic electrolytes like conventional liquid lithium-ion secondary batteries will not occur in principle. In addition, if high-potential / large-capacity positive electrode materials and large-capacity negative electrode materials are usually used, a substantial increase in the output density and energy density of the battery can be achieved.

[0006] In the past, as one type of all-solid-state lithium secondary battery, a so-called lithium precipitation type all-solid-state lithium secondary battery is known in which lithium metal is precipitated on the negative electrode collector during charging. During the charging process of such a lithium precipitation type all-solid-state lithium secondary battery, lithium metal is precipitated between the solid electrolyte layer and the negative electrode collector.

[0007] In the past, as a technology for improving the charge and discharge characteristics such as the discharge capacity density and cycle characteristics of an all-solid-state lithium secondary battery, Japanese Patent Gazette No. 2014-93156 disclosed a sheet electrode formed by stacking an electrode active material layer containing a particulate electrode active material, a conductive resin layer, and a collector layer. In an embodiment of the same document, the positive electrode of a lithium precipitation-type all-solid-state lithium secondary battery using the above-mentioned sheet electrode was disclosed. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The inventors of the present invention have also studied the technology described in the above-mentioned document in the process of developing technology to improve the rapid charging characteristics of lithium secondary batteries. However, according to the research of the inventors of the present invention, it has been found that even if the technology described in the above-mentioned document is used, there are cases where sufficient rapid charging characteristics cannot be achieved.

[0010] Therefore, an object of the present invention is to provide a means for achieving rate characteristics that can cope with rapid charging in a lithium deposition type lithium secondary battery.

[0011] Solutions for solving problems

[0012] The present inventors have conducted in-depth research to solve the above problems. As a result, it was found that in a lithium secondary battery of lithium precipitation type, a conductive layer is not only arranged on the main surface opposite to the solid electrolyte layer by the negative electrode collector, but also includes a G band peak intensity (I G ) and D band peak intensity (I D ) is more intense than R(I G / I D ) is carbon particles above the specified value, which can solve the above-mentioned problems and thus complete the present invention.

[0013] That is, one embodiment of the present invention relates to a lithium secondary battery having a power generation element, wherein the power generation element comprises: a positive electrode having a positive electrode active material layer disposed on the surface of a positive electrode current collector, the positive electrode active material layer containing a positive electrode active material capable of absorbing, storing and releasing lithium ions; a negative electrode having a negative electrode current collector and on which lithium metal is precipitated during charging; and a solid electrolyte layer, which is sandwiched between the positive electrode and the negative electrode and contains a solid electrolyte. Furthermore, it is characterized in that: in the lithium secondary battery, the negative electrode current collector is provided with a carbon particle layer on at least a portion of the main surface opposite to the solid electrolyte layer, where the positive electrode active material layer and the negative electrode current collector are opposite, and the carbon particle layer contains a G band peak intensity (I G ) and D band peak intensity (I D ) is more intense than R(I G / I D ) is carbon particles of 7 or more. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a perspective view showing the appearance of a flat laminated all-solid lithium secondary battery as one embodiment of the present invention.

[0015] Figure 2 For along Figure 1 The cross-sectional view of line 2-2 is shown. It should be noted that Figure 2A cross-sectional view showing a stacked secondary battery during charging.

[0016] Figure 3 This is an enlarged cross-sectional view of a single cell layer of a stacked secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION

[0017] One embodiment of the present invention is a lithium secondary battery with a power generation element, wherein the power generation element comprises: a positive electrode having a positive electrode active material layer disposed on the surface of a positive electrode current collector, the positive electrode active material layer containing a positive electrode active material capable of absorbing, storing and releasing lithium ions; a negative electrode having a negative electrode current collector and on which lithium metal is precipitated during charging; and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode and containing a solid electrolyte, wherein the negative electrode current collector has a carbon particle layer disposed on at least a portion of a main surface opposite to the solid electrolyte layer and in a region where the positive electrode active material layer and the negative electrode current collector face each other, the carbon particle layer containing a G band peak intensity (I G ) and D band peak intensity (I D ) is more intense than R(I G / I D ) is 7 or more. According to the present invention, in a lithium deposition type lithium secondary battery, rate characteristics capable of responding to rapid charging can be exhibited.

[0018] Hereinafter, the present embodiment will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the scope of the claims and is not limited to the following embodiments. It should be noted that the dimensional ratios of the drawings may be exaggerated for the purpose of description and may differ from the actual ratios.

[0019] Figure 1 It is a perspective view showing the appearance of a flat laminated all-solid lithium secondary battery (hereinafter, also simply referred to as a “laminated secondary battery”) as one embodiment of the present invention. Figure 2 For along Figure 1 The cross-sectional view of line 2-2 is shown. It should be noted that Figure 2 A cross-sectional view showing a stacked secondary battery during charging.

[0020] like Figure 1 As shown, the stacked secondary battery 10a has a flat rectangular shape, and the negative electrode collector plate 25 and the positive electrode collector plate 27 for extracting electricity are led out from both sides. The power generation element 21 is wrapped by the battery outer packaging material (laminated film 29) of the stacked secondary battery 10a, and the surrounding is heat-welded. The power generation element 21 is sealed in a state where the negative electrode collector plate 25 and the positive electrode collector plate 27 are led out to the outside. It should be noted that Figure 1The current collector plates (25, 27) shown may be configured such that the negative current collector plate 25 and the positive current collector plate 27 are led out from the same side, or may be configured such that the negative current collector plate 25 and the positive current collector plate 27 are divided into a plurality of pieces and led out from respective sides.

[0021] like Figure 2 As shown, during charging, the power generation element 21 of the stacked secondary battery 10a of this embodiment has a structure of stacked negative electrode, solid electrolyte layer 17 and positive electrode, wherein the negative electrode has negative electrode active material layer 13 containing lithium metal arranged on both sides of the negative electrode collector 11', and the positive electrode has positive electrode active material layer 15 containing lithium transition metal composite oxide arranged on both sides of the positive electrode collector 11". Specifically, one negative electrode active material layer 13 and the adjacent positive electrode active material layer 15 are stacked in the order of negative electrode, solid electrolyte layer and positive electrode in a manner of sandwiching the solid electrolyte layer 17 and facing each other. Thus, the adjacent negative electrode, solid electrolyte layer and positive electrode constitute a single battery layer 19. Therefore, it can also be said that Figure 2 The stacked secondary battery 10 a shown has a structure in which a plurality of single cell layers 19 are stacked and electrically connected in parallel.

[0022] The negative electrode collector 11' and the positive electrode collector 11" have the following structure: a negative electrode collector plate 25 and a positive electrode collector plate 27 that are electrically connected to each electrode (negative electrode and positive electrode) are respectively installed, and are led out to the outside of the laminate film 29 in a manner of being clamped at the end of the laminate film 29. The negative electrode collector plate 25 and the positive electrode collector plate 27 can be respectively installed on the negative electrode collector 11' and the positive electrode collector 11" of each electrode through ultrasonic welding, resistance welding, etc. via a negative terminal lead and a positive terminal lead (not shown) as required.

[0023] Figure 3 FIG. 1 is an enlarged cross-sectional view of a single cell layer 19 of a stacked secondary battery according to an embodiment of the present invention. Figure 3 As shown, the single cell layer 19 constituting the stacked secondary battery 10a of this embodiment has a positive electrode composed of a positive electrode collector 11" and a positive electrode active material layer 15 arranged on the surface thereof. In addition, a solid electrolyte layer 17 containing a solid electrolyte is arranged on the surface of the positive electrode active material layer 15 opposite to the positive electrode collector 11". Here, Figure 3In the embodiment shown, the outer peripheral edge of the solid electrolyte layer 17 extends over the entire circumference and to the side of the positive electrode active material layer 15. As a result, the positive electrode active material layer 15 is configured to be one circle smaller than the solid electrolyte layer 17. That is, when the power generation element 21 is viewed from above, the entire circumference of the outer peripheral end of the positive electrode active material layer 15 is configured to be located inside the outer peripheral end of the solid electrolyte layer 17. By setting such a configuration, even if the lithium metal constituting the negative electrode active material layer 13 is squeezed from the outer peripheral end of the solid electrolyte layer 17 to the positive electrode active material layer 15 side due to the restraining pressure caused by the pressurizing member, the lithium metal becomes less likely to contact the side of the positive electrode active material layer 15. As a result, a lithium secondary battery with a higher effect of preventing short circuits is obtained. It should be noted that the "side of the positive electrode active material layer" refers to the surface that is not opposite to the negative electrode collector among the surfaces of the positive electrode active material layer that are not in contact with the positive electrode collector.

[0024] In addition, Figure 3 In the embodiment shown, the negative electrode current collector 11' is provided with a layer having an intensity ratio R (I G / I D ) is a graphene layer 18 (carbon particle layer) of graphene particles with relatively large size (the details of the intensity ratio R will be described later). The presence of the graphene layer 18 (carbon particle layer) on the surface of the negative electrode current collector 11' improves the contact between the lithium metal as the negative electrode active material layer 13 and the negative electrode current collector 11' and improves the diffusivity of lithium ions in the surface direction. As a result, during the charging process at a high rate such as during fast charging, the lithium metal as the negative electrode active material layer 13 can be uniformly precipitated, and sufficient battery performance can be maintained. Therefore, it can be said that the graphene layer 18 (carbon particle layer) plays the role of a lithium diffusion layer.

[0025] Furthermore, the solid electrolyte layer 17 is provided with a carbon black layer 22 containing carbon black nanoparticles on the entire surface of the main surface opposite to the negative electrode collector 11' and the entire surface of the side surface of the solid electrolyte layer 17. Since the carbon black constituting the carbon black layer 22 has lithium ion conductivity, the carbon black layer 22 can conduct lithium ions. Therefore, by configuring the carbon black layer 22, the battery reaction is not hindered. In addition, the carbon black layer 22 has the following function: suppressing the reaction of the lithium metal (negative electrode active material layer 13) precipitated on the negative electrode collector 11' during charging with the solid electrolyte contained in the solid electrolyte layer 17. Therefore, it can be said that the carbon black layer 22 plays the role of an ion conductivity reaction inhibition layer. It should be noted that the "side surface of the solid electrolyte layer" refers to the surface of the solid electrolyte layer that is not opposite to any of the positive electrode active material layer and the negative electrode collector when there is no discharge of the negative electrode active material layer 13 formed by lithium metal. By also disposing such a carbon black layer 22 on the side of the solid electrolyte layer 17, it is possible to prevent the lithium metal precipitated on the surface of the negative electrode collector 11' from being squeezed out from the outer peripheral end of the solid electrolyte layer 17 due to the restraining pressure of the pressurizing member during charging, and from contacting the solid electrolyte layer 17 and the negative electrode active material layer 13. In addition, since the effective area of ​​the lithium metal facing the positive electrode active material layer 15 is increased due to the carbon black layer 22 and the solid electrolyte layer 17, there is an advantage that the charge and discharge efficiency can also be further improved.

[0026] In addition, Figure 3 In the embodiment shown, the carbon black layer 22 is provided with a magnesium layer 23 containing a magnesium salt on the entire surface of the main surface opposite to the negative electrode collector 11'. The presence of the magnesium layer 23 has the advantage of further improving the high rate characteristics (resistance to rapid charging). This is because, by interposing the magnesium layer 23 between the carbon black layer 22 and the negative electrode collector 11', the energy when lithium ions are precipitated as lithium metal during the charging process can be reduced, and as a result, it is believed that charging and discharging can be performed at a higher current density. Therefore, it can be said that the magnesium layer 23 plays the role of a lithium precipitation energy reduction layer.

[0027] In the stacked secondary battery 10a of this embodiment, it is preferable that Figure 1The power generation element 21 sealed by the laminated film 29 shown and the power generation element 21 sealed by the laminated film 29 are clamped by two plate-like members and then joined using a connecting member. Thus, the plate-like member and the connecting member act as a pressure member for pressurizing (constraining) the power generation element 21 in its stacking direction. As the plate-like member, metal plates, resin plates, etc. can be listed. In addition, as the connecting member, bolts and nuts can be listed. However, there is no particular limitation on the pressure member as long as it is a member that can pressurize the power generation element 21 in its stacking direction. As a pressure member, a combination of a plate formed of a rigid material such as a plate-like member and the above-mentioned connecting member is representative. In addition, for the connecting member, not only bolts and nuts, but also tension plates that fix the ends of the plate-like member in a manner that constrains the power generation element 21 in its stacking direction can be used. It should be noted that the lower limit of the load applied to the power generation element 21 (the constraint pressure in the stacking direction of the power generation element) is, for example, 0.1 MPa or more, preferably 1 MPa or more, more preferably 3 MPa or more, and further preferably 5 MPa or more. The upper limit of the constraint pressure in the stacking direction of the power generation element is, for example, 100 MPa or less, preferably 70 MPa or less, more preferably 40 MPa or less, and further preferably 10 MPa or less.

[0028] Hereinafter, main components of the above-mentioned stacked secondary battery 10a will be described.

[0029] [Positive electrode collector]

[0030] The positive electrode collector is a conductive member that serves as a flow path for electrons released from the positive electrode to an external load or flowing from a power source to the positive electrode as the battery reaction (charge and discharge reaction) proceeds. There is no particular restriction on the material constituting the positive electrode collector. As the constituent material of the positive electrode collector, for example, metal or conductive resin can be used. There is no particular restriction on the thickness of the positive electrode collector, but as an example, it is 10 to 100 μm.

[0031] [Positive electrode active material layer]

[0032] The positive electrode constituting the lithium secondary battery of the present embodiment has a positive electrode active material layer containing a positive electrode active material capable of absorbing and releasing lithium ions.

[0033] There are no particular restrictions on the positive electrode active material as long as it is a material that can release lithium ions during the charging process of the secondary battery and absorb lithium ions during the discharge process. There are no particular restrictions on the type of positive electrode active material, and examples include: LiCoO2, LiMnO2, LiNiO2, LiVO2, Li(Ni-Mn-Co)O2 and other layered rock salt active materials, LiMn2O4, LiNi 0.5 Mn1.5 O4 and other spinel active materials, LiFePO4, LiMnPO4 and other olivine active materials, Li2FeSiO4, Li2MnSiO4 and other Si-containing active materials, etc. In addition, examples of oxide active materials other than the above include Li4Ti5O 12 . Among them, it is preferred to use a composite oxide containing lithium and nickel, and it is further preferred to use Li(Ni-Mn-Co)O2 and oxides in which a part of these transition metals is replaced by other elements (hereinafter, also referred to as "NMC composite oxide"). NMC composite oxide has a layered crystalline structure in which lithium atomic layers and transition metal (Mn, Ni and Co are regularly arranged) atomic layers are alternately stacked with oxygen atomic layers sandwiched between them. Each atom of the transition metal M contains one Li atom, and the amount of Li extracted is twice that of spinel lithium manganese oxide, that is, the supply capacity is doubled, and high capacity can be maintained.

[0034] As described above, NMC composite oxides also include composite oxides in which a part of transition metal elements is replaced by other metal elements. In this case, other elements include Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, Zn, etc., preferably Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, more preferably Ti, Zr, P, Al, Mg, Cr, and from the viewpoint of improving cycle characteristics, more preferably Ti, Zr, Al, Mg, Cr.

[0035] Furthermore, the use of a sulfur-based positive electrode active material is also one of the preferred embodiments. Examples of the sulfur-based positive electrode active material include particles or films of organic sulfur compounds or inorganic sulfur compounds, as long as they can release lithium ions during charging and absorb lithium ions during discharging by utilizing the redox reaction of sulfur.

[0036] Depending on the situation, two or more positive electrode active materials may be used in combination. Of course, positive electrode active materials other than those described above may also be used.

[0037] The shape of the positive electrode active material can be, for example, granular (spherical, fibrous), thin film, etc. When the positive electrode active material is in a particle shape, its average particle size (D50) is, for example, preferably in the range of 1nm to 100μm, more preferably in the range of 10nm to 50μm, further preferably in the range of 100nm to 20μm, and particularly preferably in the range of 1 to 20μm. It should be noted that in this specification, the value of the average particle size (D50) can be measured by a laser diffraction scattering method.

[0038] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is, for example, preferably in the range of 30 to 99 mass %, more preferably in the range of 40 to 90 mass %, and further preferably in the range of 45 to 80 mass %.

[0039] In the lithium secondary battery of this embodiment, the positive electrode active material layer 15 preferably further includes a solid electrolyte. Examples of the solid electrolyte include sulfide solid electrolytes, resin solid electrolytes, and oxide solid electrolytes. It should be noted that in this specification, the solid electrolyte refers to a material composed mainly of an ion conductor that can conduct ions in a solid, and in particular refers to a material having a lithium ion conductivity of 1×10 -5 S / cm or more, the lithium ion conductivity is preferably 1×10 -4 Here, the value of ion conductivity can be measured by an AC impedance method.

[0040] In other preferred embodiments of the secondary battery of the present invention, the solid electrolyte is preferably a sulfide solid electrolyte containing the S element, more preferably a sulfide solid electrolyte containing the Li element, the M element and the S element, from the viewpoint of being able to exhibit excellent lithium ion conductivity and being able to further track the volume change of the electrode active material accompanying charge and discharge, and the M element contains at least one element selected from the group consisting of P, Si, Ge, Sn, Ti, Zr, Nb, Al, Sb, Br, Cl and I. A sulfide solid electrolyte containing the S element, the Li element and the P element is further preferred.

[0041] The sulfide solid electrolyte may have a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. In addition, examples of sulfide solid electrolytes having a Li4P2S7 skeleton include a Li-PS-based solid electrolyte called LPS. In addition, examples of sulfide solid electrolytes include Li (4-x) Ge (1-x) P x S4 (x satisfies 0<x<1) represented by LGPS, etc. More specifically, examples thereof include: LPS (Li2S-P2S5), Li7P3S 11 , Li 3.2 P 0.96 S. Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12, or Li6PS5X (where X is Cl, Br or I), etc. It should be noted that the description of "Li2S-P2S5" refers to a sulfide solid electrolyte made using a raw material composition containing Li2S and P2S5, and the same applies to other records. Among them, from the perspective of high ionic conductivity and low bulk elastic modulus, which can further track the volume change of the electrode active material with charge and discharge, the sulfide solid electrolyte is preferably selected from LPS (Li2S-P2S5), Li6PS5X (where X is Cl, Br or I), Li7P3S 11 , Li 3.2 P 0.96 A group composed of S and Li3PS4.

[0042] The content of the solid electrolyte in the positive electrode active material layer is not particularly limited, but is, for example, preferably in the range of 1 to 70 mass %, more preferably in the range of 10 to 60 mass %, and further preferably in the range of 20 to 55 mass %.

[0043] The positive electrode active material layer may contain at least one of a conductive aid and a binder in addition to the positive electrode active material and the solid electrolyte. The thickness of the positive electrode active material layer varies depending on the structure of the target lithium secondary battery, and is preferably within the range of 0.1 to 1000 μm, and more preferably 40 to 100 μm.

[0044] [Solid electrolyte layer]

[0045] The solid electrolyte layer is a layer interposed between the positive electrode active material layer and the negative electrode current collector, and contains a solid electrolyte (usually as a main component). The specific form of the solid electrolyte contained in the solid electrolyte layer is the same as described above, so detailed description is omitted here.

[0046] The content of the solid electrolyte in the solid electrolyte layer is, for example, preferably in the range of 10 to 100 mass %, more preferably in the range of 50 to 100 mass %, and further preferably in the range of 90 to 100 mass %, relative to the total mass of the solid electrolyte layer.

[0047] The solid electrolyte layer may contain a binder in addition to the above-mentioned solid electrolyte.

[0048] The thickness of the solid electrolyte layer varies depending on the structure of the target lithium secondary battery, but is preferably within a range of 0.1 to 1000 μm, and more preferably 10 to 40 μm, for example.

[0049] [Negative electrode current collector]

[0050] The negative electrode current collector is a conductive member that serves as a flow path for electrons released from the negative electrode to the power source or flowing from the external load to the negative electrode as the battery reaction (charge and discharge reaction) proceeds. The material constituting the negative electrode current collector is not particularly limited. As the constituent material of the negative electrode current collector, for example, metals and conductive resins can be used. There is no particular limitation on the thickness of the negative electrode current collector, and as an example, it is 10 to 100 μm.

[0051] [Negative Electrode Active Material Layer]

[0052] The lithium secondary battery of this mode is a so-called lithium precipitation type secondary battery in which lithium metal is precipitated on the negative electrode collector during the charging process. During the charging process, the layer formed by the lithium metal precipitated on the negative electrode collector is the negative electrode active material layer of the lithium secondary battery of this mode. Therefore, the thickness of the negative electrode active material layer increases as the charging process proceeds, and the thickness of the negative electrode active material layer decreases as the discharging process proceeds. The negative electrode active material layer may not exist during full discharge, but depending on the circumstances, a certain degree of negative electrode active material layer formed by lithium metal may be configured during full discharge. In addition, the thickness of the negative electrode active material layer (lithium metal layer) during full charge is not particularly limited, and is usually 0.1 to 1000 μm.

[0053] [Carbon particle layer]

[0054] In the lithium secondary battery of this embodiment, the negative electrode current collector is provided with a carbon particle layer containing carbon particles on at least a portion of the region where the positive electrode active material layer and the negative electrode current collector are opposite to each other on the main surface opposite to the solid electrolyte layer. Here, the carbon particle layer contains a G band peak intensity (I G ) and D band peak intensity (I D ) is more intense than R(I G / I D ) is carbon particles of 7 or more.

[0055] Generally, when analyzing carbon materials by Raman spectroscopy, the -1 Nearby and 1582cm -1 There is a peak near 1582cm. Carbon materials with high crystallinity such as graphene and graphite have a peak at 1582cm -1 There is a strong peak near 1350cm, which is usually called the "G band". On the other hand, as the crystallinity decreases (the crystal structure defects increase), there is a strong peak at 1350cm -1 This peak is usually called the "D band" (it should be noted that the peak of diamond is strictly 1333cm -1 , which is different from the above-mentioned D band). The peak intensity of the G band (I G ) and D band peak intensity (I D ) is more intense than R(I G / ID ) is used as an indicator of the degree of crystallinity of the carbon material. It should be noted that in this embodiment, the intensity ratio R (I G / I D ) is calculated by measuring the Raman spectrum of the carbon particles contained in the carbon particle layer using a micro-Raman spectrometer. When the carbon particle layer contains carbon particles with different intensity ratios R, it can be calculated as a weighted average of the intensity ratios R weighted by the mass of each type of carbon particle.

[0056] As described above, in this embodiment, it is necessary that the strength ratio R of the carbon particles contained in the carbon particle layer is 7 or more. In addition, in a preferred embodiment, the strength ratio R of the carbon particles contained in the carbon particle layer is 25 or more, more preferably 50 or more, further preferably 500 or more, even more preferably 2000 or more, particularly preferably 5000 or more, and most preferably 8000 or more. There is no particular limitation on the upper limit of the strength ratio R, but it is usually 100000 or less.

[0057] As the carbon material constituting the carbon particles contained in the carbon particle layer, any carbon material that exhibits the strength ratio R as described above can be used without particular limitation. Among them, as a carbon material that particularly exhibits a high strength ratio R, a carbon material formed by a graphene layer can be cited. There is no particular limitation on the number of stacking graphene layers constituting these carbon materials. In this specification, a flaky carbon material having a stacking number of up to 10 graphene layers is referred to as "graphene". In addition, in graphene, a graphene layer having a stacking number of 1 is referred to as "single-layer graphene", and a graphene layer having a stacking number of 2 to 10 is referred to as "multi-layer graphene". Furthermore, a flaky carbon material having a stacking number of 11 or more graphene layers is referred to as "graphite". Here, as an example, the number of stacking graphene layers constituting the above-mentioned carbon material is preferably 1 to 100 layers, more preferably 2 to 50 layers, further preferably 3 to 20 layers, and particularly preferably 4 to 10 layers. Therefore, the carbon particles contained in the carbon particle layer of the present embodiment preferably contain graphene or graphite, and more preferably contain graphene. Graphene or graphite (especially graphene) is a carbon material with high crystallinity as shown by the high strength ratio R. Therefore, it can effectively contribute to improving the contact between the lithium metal and the negative electrode current collector as the negative electrode active material layer and improving the diffusibility of the surface direction of lithium ions. It should be noted that as the carbon particles contained in the carbon particle layer, only one kind can be used alone, or two or more kinds can be used in combination. In addition, as carbon materials other than the above, for example, carbon black, diamond (for example, boron-doped diamond), fullerene, carbon nanotube, carbon nanofiber (vapor-deposited carbon fiber (VGCF, etc.)), carbon nanohorn, carbon microcoil, carbon nanocoil, etc. can be listed. As carbon particles, commercial products or processed products of commercial products can be used, and self-prepared materials can also be used. Since the above-mentioned multilayer graphene and graphite manufacturing methods are widely known, detailed descriptions are omitted here. However, as an example, the intensity ratio R can be controlled by changing the calcination temperature of graphite, which is a precursor when producing carbon particles.

[0058] The content of the carbon particles in the carbon particle layer is not particularly limited, but is preferably 50 to 100 mass %, more preferably 80 to 99 mass %, and even more preferably 90 to 98 mass % relative to 100 mass % of the total amount of the constituents of the carbon particle layer.

[0059] The carbon particle layer of this method may further contain a binder in addition to the carbon particles. Examples of the binder include: polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (compounds containing hydrogen atoms substituted by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene / butadiene rubber (SBR), ethylene / propylene / diene copolymer, styrene / butadiene / styrene block copolymer and its hydrogenate, styrene / isoprene / styrene block copolymer and its hydrogenate, and other thermoplastic polymers, tetrafluoroethylene / hexafluoropropylene copolymer (FEP), tetrafluoroethylene / perfluoroalkyl vinyl ether copolymer (PFA), ethylene / tetrafluoroethylene copolymer (ETFE ), polytrifluorochloroethylene (PCTFE), ethylene / chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF) and other fluororesins, vinylidene fluoride-hexafluoropropylene fluororubber (VDF-HFP fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene fluororubber (VDF-HFP-TFE fluororubber), vinylidene fluoride-pentafluoropropylene fluororubber (VDF-PFP fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene fluororubber (VDF-PFP-TFE fluororubber), vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene fluororubber (VDF-PFMVE-TFE fluororubber), vinylidene fluoride-chlorotrifluoroethylene fluororubber (VDF-CTFE fluororubber) and other vinylidene fluoride fluororubbers, epoxy resins, etc. Among them, polyvinylidene fluoride (PVDF) (compounds containing hydrogen atoms replaced by other halogen elements), polyimide, styrene / butadiene rubber, carboxymethyl cellulose, polypropylene, polytetrafluoroethylene, polyacrylonitrile, polyamide are preferably used.

[0060] The content of the binder in the carbon particle layer is not particularly limited, but is preferably 50% by mass or less, more preferably 1 to 20% by mass, and further preferably 2 to 10% by mass, relative to 100% by mass of the total amount of the constituents of the carbon particle layer.

[0061] There is no particular limitation on the average thickness of the carbon particle layer, and the carbon particle layer can be configured with a thickness that can achieve the above-mentioned performance. As an example, the average thickness of the carbon particle layer is preferably 10 nm to 10 μm, more preferably 50 nm to 6 μm, and further preferably 1 to 4 μm. It should be noted that the "average thickness" of the carbon particle layer refers to the value calculated as the arithmetic mean of the thicknesses measured at several to a dozen different locations of the carbon particle layer.

[0062] Among the carbon particles contained in the carbon particle layer, the proportion of particles whose long axes are oriented in the surface direction of the carbon particle layer is preferably 80% or more, more preferably 85% or more, particularly preferably 90% or more, and most preferably 95% or more (the upper limit is 100%). By orienting the carbon particles in the surface direction in this way, the diffusion of lithium ions in the surface direction can be further improved. It should be noted that the above ratio is set to a value calculated by the method described in the column of the examples described later (observation of a cross-sectional image using a scanning electron microscope (SEM)).

[0063] In addition, the surface roughness of the main surface of the solid electrolyte layer side of the carbon particle layer (maximum height specified in JIS B0601-2001; Rz) is preferably 15 μm or less, more preferably 12 μm or less, particularly preferably 10 μm or less, and most preferably 8 μm or less. If the maximum height (Rz) of the surface of the carbon particle layer is a value in such a range, local current concentration is not likely to occur during charge and discharge. As a result, the contact between the lithium metal as the negative electrode active material layer and the negative electrode collector can be further improved.

[0064] Furthermore, the peel strength between the carbon particle layer and the negative electrode current collector is preferably 5 N / m or more, more preferably 10 N / m or more, and further preferably 15 N / m or more. If the peel strength between the carbon particle layer and the negative electrode current collector is within such a range, lithium metal precipitation is unlikely to occur at the interface between the carbon particle layer and the negative electrode current collector during the charging process, and lithium metal can be reliably precipitated at the interface between the carbon particle layer and the solid electrolyte layer, resulting in further improvement of the rapid charging characteristics.

[0065] The carbon particle layer can be like Figure 3 As shown in FIG. 1 , the negative electrode current collector may be disposed on the entire surface thereof, or may be disposed on a portion of the surface thereof. Figure 3 Furthermore, by providing the carbon particle layer only at a location where lithium metal is to be deposited (a portion of the surface of the negative electrode current collector), the carbon particle layer can be used efficiently.

[0066] There is no particular limitation on the relationship between the size of the carbon particle layer and the size of the solid electrolyte layer when the power generation element is viewed from above in the stacking direction. Figure 3 As shown, in a top view of the power generation element, the outer peripheral end of the carbon particle layer (graphene layer 18) is preferably located inside the outer peripheral end of the solid electrolyte layer 17. By setting such a structure, it is possible to effectively prevent the lithium metal precipitated during charging from bypassing the outer peripheral end of the solid electrolyte layer and short-circuiting with the positive electrode active material layer.

[0067] There is no particular restriction on the method for forming a carbon particle layer as described above on the surface of the negative electrode collector. For example, the following method can be used: a slurry in which the above-mentioned carbon particles and a binder as required are dispersed in a suitable solvent is applied to the surface of the negative electrode collector, and the solvent is dried. In addition, the above-mentioned slurry can also be applied to the surface of a support such as a stainless steel foil and the solvent is dried to obtain a coating film, and the obtained coating film is bonded to the surface of the negative electrode collector using a hydraulic press or the like, and then the support is peeled off to form it. In addition, with respect to the carbon particle layer, it is effective to form a carbon particle layer on the surface of the negative electrode collector by the above-mentioned method within the scope of a preferred embodiment, and then the obtained laminate is subjected to a rolling treatment using a roller press. The detailed description of the rolling treatment using a roller press is omitted, but the various parameters mentioned above can be appropriately controlled by adjusting the pressing pressure (line pressure) during the rolling treatment, the number of treatments, the mixing ratio of carbon particles and the binder, etc.

[0068] [Ion-conductive reaction suppression layer]

[0069] In the lithium secondary battery of this embodiment, Figure 3 As shown, it is preferred that the solid electrolyte layer 17 is provided with an ion conductive reaction inhibiting layer (carbon black layer 22) on at least a portion of the region where the positive electrode active material layer 15 and the negative electrode current collector 11' are opposite to each other on the main surface opposite to the negative electrode current collector 11'. The ion conductive reaction inhibiting layer is a layer having lithium ion conductivity and inhibiting the reaction between lithium metal (negative electrode active material layer) and the solid electrolyte. Therefore, by providing the ion conductive reaction inhibiting layer, the battery reaction is not hindered, and the degradation of the solid electrolyte and the reduction of the battery capacity caused by the reaction between lithium metal (negative electrode active material layer) and the solid electrolyte can be prevented.

[0070] Here, a material "has lithium ion conductivity" means that the lithium ion conductivity of the material at 25°C is 1×10 -4 On the other hand, a material “does not have lithium ion conductivity” means that the lithium ion conductivity of the material at 25°C is less than 1×10 -4 [S / cm]. In the lithium secondary battery of this embodiment, the constituent material of the ion conductive reaction suppression layer has a lithium ion conductivity of 1×10 -4 [S / cm] or more, preferably 1.5×10 -4 [S / cm] or more, more preferably 2.0×10 -4 [S / cm] or more, more preferably 2.5×10 -4 [S / cm] or more, particularly preferably 3.0×10 -4 [S / cm] or more.

[0071] There is no particular restriction on the constituent material of the ion-conducting reaction inhibition layer, and various materials that can exhibit the above-mentioned functions can be used. As an example of the constituent material of the ion-conducting reaction inhibition layer, nanoparticles having lithium ion conductivity can be listed (in this specification, nanoparticles as the constituent material of the ion-conducting reaction inhibition layer are also referred to as "first nanoparticles"). The ion-conducting reaction inhibition layer can provide a lithium secondary battery with particularly excellent functions of the ion-conducting reaction inhibition layer by including the first nanoparticles. Here, "nanoparticles" refer to particles having an average particle size of nanometer (nm) level. In addition, the "average particle size" of the nanoparticles refers to the 50% cumulative diameter (D50) of the particle size (the largest distance between any two points on the observed contour line of the particles) measured by observing the cross-section of the layer containing the nanoparticles using a scanning electron microscope (SEM). The average particle size of the first nanoparticle is preferably less than 500nm, more preferably less than 300nm, further preferably less than 150nm, particularly preferably less than 100nm, and most preferably less than 60nm. In particular, if the average particle size of the first nanoparticles is 60 nm or less, a lithium secondary battery having a particularly excellent dendrite growth inhibition effect can be provided. It should be noted that there is no particular restriction on the lower limit of the average particle size of the first nanoparticles, which is usually 10 nm or more, preferably 20 nm or more.

[0072] From the viewpoint of being particularly excellent in function as an ion conductive reaction inhibiting layer, such a first nanoparticle, for example, preferably comprises one or more elements selected from the group consisting of carbon, gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin and zinc, and is more preferably formed by one or more of a single substance or alloy of these elements. In addition, the first nanoparticle preferably comprises carbon, and is more preferably formed by a single substance of carbon. As such a material formed by a single substance of carbon, for example, acetylene black, VULCAN (registered trademark), BLACK PEARLS (registered trademark), carbon nanofibers, Ketjen black (registered trademark), carbon nanotubes, carbon nanohorns, carbon nanospheres and fullerenes can be cited. It should be noted that when the ion conductive reaction inhibiting layer comprises such nanoparticles, the layer may also comprise a binder.

[0073] There is no particular limitation on the method of forming an ion-conducting reaction inhibition layer containing the first nanoparticles as described above on the surface of the negative electrode collector side of the solid electrolyte layer. For example, the following method can be used: a slurry in which the nanoparticles and an adhesive as required are dispersed in a suitable solvent is applied to the surface of the negative electrode collector side of the solid electrolyte layer, and the solvent is dried. In addition, a coating film can be obtained by applying the slurry to the surface of a support such as a stainless steel foil and drying the solvent, and the obtained coating film is bonded to the surface of the negative electrode collector side of the solid electrolyte layer using a method such as a hydraulic press, and then the support is peeled off to form an ion-conducting reaction inhibition layer. It should be noted that, depending on the circumstances, a continuous layer containing any of the above-mentioned materials can be formed by sputtering or the like instead of nanoparticles, thereby serving as an ion-conducting reaction inhibition layer.

[0074] The first nanoparticles constituting the ion conductive reaction suppression layer are described above, and the ion conductive reaction suppression layer including the first nanoparticles generally has electron conductivity. If the ion conductive reaction suppression layer has electron conductivity, the resistance to rapid charging can be further improved, which is preferred.

[0075] However, it is also one of the preferred embodiments that the ion conductive reaction inhibition layer is electronically insulating. If the ion conductive reaction inhibition layer is electronically insulating, the side reaction between the solid electrolyte layer and lithium metal can be more reliably prevented compared with the case of electronic conductivity due to its high stability to lower potentials, which can help to effectively improve the durability of the battery cell. As the electronically insulating constituent material of the ion conductive reaction inhibition layer, for example, there can be listed: a composite metal oxide represented by a lithium halide (lithium fluoride (LiF), lithium chloride (LiCl), lithium bromide (LiBr), lithium iodide (LiI)), Li-MO (M is a metal element selected from the group consisting of Mg, Au, Al, Sn and Zn), and one or more lithium-containing compounds in the group consisting of Li-Ba-TiO3 composite oxides. Any of these materials is more stable than a solid electrolyte for reduction decomposition caused by contact with lithium metal. That is, the tendency of the solid electrolyte constituting the solid electrolyte layer to be reductively decomposed due to contact with lithium metal is smaller than the tendency of the above-mentioned lithium-containing compound as a constituent material of the ion-conducting reaction inhibition layer to be reductively decomposed due to contact with lithium metal. Therefore, the above-mentioned lithium-containing compound can also play a role as an ion-conducting reaction inhibition layer. There is no particular limitation on the method for forming an ion-conducting reaction inhibition layer containing such a lithium-containing compound. For example, a continuous layer containing the above-mentioned lithium-containing compound can be formed by a method such as sputtering to form an ion-conducting reaction inhibition layer.

[0076] There is no particular restriction on the average thickness of the ion-conducting reaction inhibition layer, as long as it is configured with a thickness that can perform the above-mentioned functions. As an example, the average thickness of the ion-conducting reaction inhibition layer is preferably 300nm to 20μm, more preferably 500nm to 15μm, and further preferably 1 to 10μm when the layer is a layer containing the first nanoparticles. In addition, when the layer is a continuous layer formed by a lithium-containing compound or the like formed by a method such as sputtering, it is preferably 0.5 to 20nm. It should be noted that the "average thickness" of the ion-conducting reaction inhibition layer refers to the value calculated as the arithmetic mean of the thicknesses of several to a dozen different positions of the ion-conducting reaction inhibition layer constituting the lithium secondary battery.

[0077] The Young's modulus of the ion-conductive reaction inhibition layer is preferably 2 GPa or more, more preferably 5 GPa or more, particularly preferably 8 GPa or more, and particularly preferably 10 GPa or more. The ion-conductive reaction inhibition layer exhibits such a high Young's modulus, and even if dendrites are generated from the precipitated lithium metal during rapid charging, the dendrites can be effectively prevented from penetrating the solid electrolyte layer and reaching the positive electrode active material layer to cause an internal short circuit. It should be noted that the value of the Young's modulus of the ion-conductive reaction inhibition layer is the value measured according to JIS K 7161-1:2014.

[0078] [Lithium deposition energy reduction layer]

[0079] In the lithium secondary battery of this embodiment, Figure 3 As shown, the ion conductive reaction inhibition layer (carbon black layer 22) is preferably provided with a lithium precipitation energy reduction layer (magnesium layer 23) on at least a portion of the main surface opposite to the negative electrode current collector 11' (preferably the entire surface of the main surface), and the lithium precipitation energy reduction layer (magnesium layer 23) contains a single substance of an element that can be alloyed with lithium or a compound containing the element. Through such a structure, when lithium metal is precipitated as a negative electrode active material layer during the charging process of the lithium secondary battery, the energy when lithium metal is precipitated as a negative electrode active material layer can be reduced by alloying with lithium through the constituent material of the lithium precipitation energy reduction layer, and charging and discharging can be performed at a higher current density. As a result, the charging capacity can be further improved even in the case of rapid charging. Here, as an element that can be alloyed with lithium contained in the lithium precipitation energy reduction layer, at least one of the group consisting of gold, silver, zinc, magnesium, aluminum, platinum, silicon, tin, bismuth, indium and palladium can be listed. In addition to the single substance of these elements, the lithium precipitation energy reduction layer can also be composed of a compound containing these elements. Examples of the compound include, in addition to salts such as chlorides, sulfates, carbonates, and nitrates: SiO x SnO xOxides, Ni-Si alloys, Ti-Si alloys, Mg-Sn alloys, Fe-Sn alloys and other alloys containing transition metal elements, etc. Among them, the single substance of the above elements or salts containing the elements are preferred, and the single substance of silver, zinc or magnesium or salts containing the elements are more preferred.

[0080] There is no particular restriction on the average thickness of the lithium deposition energy reduction layer, as long as it is configured with a thickness that can perform the above-mentioned functions. As an example, the average thickness of the lithium deposition energy reduction layer is preferably 10nm to 10μm, more preferably 50nm to 6μm, and further preferably 1 to 4μm. It should be noted that the "average thickness" of the lithium deposition energy reduction layer refers to the value calculated as the arithmetic mean of the thickness of several to a dozen different positions of the lithium deposition energy reduction layer.

[0081] Above, the case where the secondary battery of this mode is an all-solid-state lithium secondary battery is illustrated, and the lithium secondary battery of this mode may not be an all-solid-state type. That is, the solid electrolyte layer may also contain a previously known liquid electrolyte (electrolyte). There is no particular restriction on the amount of the liquid electrolyte (electrolyte) that may be contained in the solid electrolyte layer, and it is preferably an amount that maintains the shape of the solid electrolyte layer formed by the solid electrolyte and does not cause leakage of the liquid electrolyte (electrolyte). It should be noted that, as a liquid electrolyte (electrolyte), a solution having a previously known lithium salt dissolved in a previously known organic solvent is used. The liquid electrolyte (electrolyte) may also contain additives other than organic solvents and lithium salts. These additives may be used alone or in combination of two or more. In addition, the amount used when using the additive in the electrolyte may be appropriately adjusted.

[0082] Example

[0083] The present invention is further described in detail below by way of examples. However, the technical scope of the present invention is not limited to the following examples. It should be noted that the following operations are performed in a glove box with an argon atmosphere having a dew point of less than -68°C. In addition, the apparatus and devices used in the glove box are fully dried in advance.

[0084] <Production Example of Evaluation Battery Cell>

[0085] [Example 1]

[0086] (Manufacturing of Positive Electrode Active Material Layer)

[0087] As the constituent material of the positive electrode active material layer, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1O2, average particle size (D50): 3μm), argyrodite-type sulfide solid electrolyte (Li6PS5Cl, average particle size (D50): 0.2μm) as solid electrolyte, carbon nanofiber (CNF) as conductive aid (Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150nm, average fiber length: about 9μm), and polytetrafluoroethylene (PTFE) as binder. In a glove box with an argon atmosphere at a dew point below -68°C, the positive electrode active material, solid electrolyte, conductive aid and binder were weighed in a mass ratio of 79:16:3:2 and kneaded in an agate mortar. After confirming that the binder has been fibrillated, the obtained mixture was formed into a sheet using a hand roller, and then punched into a square of 19 mm square to obtain a positive electrode active material layer with a thickness of 100μm.

[0088] (Manufacturing of Solid Electrolyte Layer)

[0089] 95 parts by mass of a argyrodite-type sulfide solid electrolyte (Li6PS5Cl) as a solid electrolyte was mixed with a binder solution (a solution prepared by dissolving 5 parts by mass of styrene-butadiene rubber (SBR) as a binder in mesitylene as a solvent) to prepare a solid electrolyte slurry. The obtained solid electrolyte slurry was applied to the surface of a stainless steel foil as a support using an applicator, and after drying, it was punched into a square of 25 mm square to obtain a solid electrolyte layer with a thickness of 30 μm.

[0090] (Manufacturing of negative electrode)

[0091] 95 parts by mass of graphene as carbon particles are mixed with a binder solution (a solution prepared by dissolving 5 parts by mass of polyvinylidene fluoride (PVdF) as a binder in N-methyl-2-pyrrolidone (NMP) as a solvent) to prepare a carbon particle slurry (solid content 5% by mass). The obtained carbon particle slurry is applied to the surface of a stainless steel foil (thickness 10 μm) as a negative electrode collector using an applicator and dried to obtain a laminate. Then, the obtained laminate is formed into a sheet by rolling the laminate using a roller press, and is punched into squares of 21 mm square to obtain a negative electrode in which a carbon particle layer is stacked on the surface of the negative electrode collector. It should be noted that in the present embodiment, the conditions of the roller press are set so that the thickness of the carbon particle layer becomes 100 nm. In addition, for the carbon particles (graphene) used in this embodiment, the G band peak intensity (I G ) and D band peak intensity (I D ) is more intense than R(I G / I DSpecifically, first, a Raman spectrum of carbon particles is measured using a micro-Raman spectrometer. Then, the Raman spectrum of carbon particles at 1500 to 1600 cm -1 (1582cm -1 The peak intensity of the band (G band) near G ) and located at 1300~1400cm -1 (1350cm -1 The peak intensity (I D ) of the peak area ratio (I G / I D ), and the intensity ratio R is set (the same below). As a result, the intensity ratio R of the above-mentioned carbon particles is 8223.

[0092] (Manufacturing of Evaluation Battery Cell)

[0093] The positive electrode active material layer and the solid electrolyte layer manufactured above are sequentially overlapped on an aluminum foil (19 mm square, 20 μm thick) as a positive electrode collector, and the stainless steel foil as a support of the solid electrolyte layer is peeled off, and cold isostatic pressing (CIP) is used for pressurization to obtain a laminate formed by a positive electrode collector / positive electrode active material layer / solid electrolyte layer. At this time, the pressing pressure during the CIP treatment is controlled in such a way that the outer peripheral edge of the solid electrolyte layer extends all around and halfway to the side of the positive electrode active material layer. Next, an ion conductive reaction inhibition layer (thickness 100 nm) formed of lithium chloride (LiCl) is formed by sputtering on the exposed surface of the solid electrolyte layer, thereby obtaining a laminate formed by a positive electrode collector / positive electrode active material layer / solid electrolyte layer / ion conductive reaction inhibition layer. At this time, the conditions for sputtering are controlled in such a way that the outer peripheral edge of the ion conductive reaction inhibition layer extends all around and halfway to the side of the solid electrolyte layer. Furthermore, the Young's modulus of the obtained ion conductive reaction suppressing layer (LiCl layer) was measured by spherical nanoindentation measurement and found to be 30 GPa.

[0094] Then, the negative electrode produced above was stacked so that the exposed surface of the carbon particle layer faced the ion conductive reaction suppression layer, and pressed by cold isostatic pressing (CIP) to produce an evaluation battery cell (lithium precipitation type all-solid lithium secondary battery).

[0095] [Example 2]

[0096] As carbon particles constituting the carbon particle layer, graphite (strength ratio R=26) was used instead of graphene, and the battery cell for evaluation of this embodiment (lithium precipitation type all-solid-state lithium secondary battery) was manufactured by the same method as in the above-mentioned embodiment 1. It should be noted that in this embodiment, the conditions for the roller press were set so that the thickness of the carbon particle layer became 3 μm.

[0097] [Example 3]

[0098] As carbon particles constituting the carbon particle layer, graphite (strength ratio R=7) was used instead of graphene, and the battery cell for evaluation of this embodiment (lithium precipitation type all-solid lithium secondary battery) was manufactured by the same method as in the above-mentioned embodiment 1. It should be noted that in this embodiment, the conditions for the roller press were set so that the thickness of the carbon particle layer became 3 μm.

[0099] [Example 4]

[0100] In the above-mentioned Example 1, as an ion conductive reaction suppression layer, a carbon black layer is used instead of a sputtered layer of lithium chloride. Specifically, 90 parts by mass of carbon black is mixed with a binder solution (a solution in which 10 parts by mass of polyvinylidene fluoride (PVdF) as a binder is dissolved in N-methyl-2-pyrrolidone (NMP) as a solvent) to prepare a carbon black slurry (solid content 5% by mass). The obtained carbon black slurry is applied to the surface of a stainless steel foil as a support using an applicator, and after drying, it is punched into squares of 21 mm square to obtain a carbon black layer with a thickness of 10 μm formed on the support. It should be noted that the Young's modulus of the obtained ion conductive reaction suppression layer (carbon black layer) was measured by spherical nanoindentation measurement, and the result was 2 GPa. Furthermore, the exposed surfaces of the positive electrode active material layer and the solid electrolyte layer manufactured above are overlapped in sequence on the aluminum foil (19 mm square) as the positive electrode collector, the stainless steel foil as the support of the solid electrolyte layer is peeled off, and then the exposed surface of the carbon black layer manufactured above is overlapped, and the stainless steel foil as the support of the carbon black layer is peeled off, and cold isostatic pressing (CIP) is used for pressurization to obtain a laminate formed by the positive electrode collector / positive electrode active material layer / solid electrolyte layer / ion conductive reaction inhibition layer. At this time, the pressing pressure during the CIP treatment is controlled in a manner that the outer peripheral edge of the solid electrolyte layer is all around and extends to the middle of the side of the positive electrode active material layer, and the outer peripheral edge of the ion conductive reaction inhibition layer is all around and extends to the middle of the side of the solid electrolyte layer. In addition, the battery cell for evaluation of this embodiment (lithium precipitation type all-solid lithium secondary battery) is manufactured by the same method as in the above-mentioned Example 1.

[0101] [Example 5]

[0102] Before bonding the negative electrode to the ion conductive reaction inhibition layer, a dispersion obtained by dispersing magnesium chloride powder in an appropriate amount of ethanol is sprayed on the exposed surface of the carbon particle layer and dried to form a lithium precipitation energy reduction layer (thickness 10nm). Then, the exposed surface of the lithium precipitation energy reduction layer in the negative electrode overlaps with the ion conductive reaction inhibition layer in a relative manner, and is pressed by cold isostatic pressing (CIP) to manufacture an evaluation battery cell (lithium precipitation type all-solid lithium secondary battery). In addition, the evaluation battery cell (lithium precipitation type all-solid lithium secondary battery) of this embodiment is manufactured by the same method as in the above-mentioned Example 1.

[0103] [Comparative Example 1]

[0104] As carbon particles constituting the carbon particle layer, the battery cell for evaluation of this comparative example (lithium precipitation type all-solid-state lithium secondary battery) was manufactured by the same method as in the above-mentioned Example 1, except that graphite (strength ratio R=4) was used instead of graphene. It should be noted that in this comparative example, the conditions of the roller press were set so that the thickness of the carbon particle layer became 3 μm.

[0105] [Comparative Example 2]

[0106] The evaluation battery cell (lithium precipitation type all-solid lithium secondary battery) of this comparative example was manufactured in the same manner as in the comparative example 1, except that the rolling process using the roller press was not performed during the manufacture of the carbon particle layer. The thickness of the obtained carbon particle layer was 7 μm.

[0107] [Comparative Example 3]

[0108] As carbon particles constituting the carbon particle layer, carbon black (strength ratio R = 0.9) was used instead of graphite, and the battery cell for evaluation of this comparative example (lithium precipitation type all-solid lithium secondary battery) was manufactured by the same method as the above-mentioned comparative example 1. It should be noted that in this comparative example, the conditions for the roller press were set so that the thickness of the carbon particle layer became 7 μm.

[0109] [Evaluation of negative electrode]

[0110] For the carbon particle layer of the negative electrode manufactured in the above-mentioned embodiment and comparative example, a cross section in the stacking direction was observed using a scanning electron microscope (SEM), and the proportion of particles whose long axis of the particles was oriented in the plane direction of the carbon particle layer (that is, the angle formed by the long axis in the plane direction was 45° or less) was measured. It should be noted that the "long axis of the particle" refers to the direction of the line segment representing the maximum distance between the two parallel straight lines when the contour of the carbon particle in the SEM cross-sectional image is clamped. As a result, in the carbon particle layer of Examples 1 to 5 and Comparative Example 1, more than 80% of the carbon particles were confirmed to be oriented in the plane direction. On the other hand, in the carbon particle layer of Comparative Example 2, although some orientation of the carbon particles in the plane direction was observed, the proportion of carbon particles oriented at 45° or less was less than 80%. In addition, in the carbon particle layer of Comparative Example 3, the carbon particles were randomly oriented, and the orientation was not particularly confirmed.

[0111] Furthermore, for the carbon particle layer of the negative electrode manufactured as described above, the Rz (maximum height) specified in JIS B 0601-2001 was measured. The results are shown in Table 1 below. In addition, for the negative electrode manufactured as described above, the peel strength between the carbon particle layer and the negative electrode collector was measured. Specifically, the negative electrode manufactured as described above was cut into 10 mm width to manufacture a sample, and the surface on the carbon particle layer side was fixed to the table using a double-sided tape. Next, a 90° peel test was performed at a peeling speed of 100 mm / min to measure the peel strength when peeling the interface of the carbon particle layer / negative electrode collector. The results are shown in Table 1 below.

[0112] [Evaluation of evaluation battery cell (measurement of charge and discharge efficiency)]

[0113] The positive electrode collector and negative electrode collector of the evaluation battery cell manufactured as described above were connected to the positive electrode lead and the negative electrode lead, respectively, and charged and discharged at a charge and discharge rate of 0.1 C or 3.5 C according to the following charge and discharge test conditions. At this time, a pressure member was used to apply a restraining pressure of 3 [MPa] in the stacking direction of the evaluation battery cell, and the following charge and discharge test was performed.

[0114] (Charge and discharge test conditions)

[0115] 1) Charge and discharge conditions

[0116] [Voltage range] 3.0~4.3V

[0117] [Charging process] CCCV (0.01C cut-off)

[0118] [Discharge process]CC

[0119] [Charge and discharge rate] 0.1C or 3.5C

[0120] (After charging and discharging, pause for 30 minutes respectively)

[0121] 2) Evaluation temperature: 333K (60°C).

[0122] The evaluation battery cell uses a charge and discharge tester. In a thermostatic chamber set to the above-mentioned evaluation temperature, during the charging process (lithium metal is deposited on the negative electrode collector), it is set to constant current / constant voltage (CCCV) mode, and charged from 3.0V to 4.3V (0.01C cutoff) at the above-mentioned rate. Then, in the discharge process (lithium metal on the negative electrode collector is dissolved), it is set to constant current (CC) mode, and discharged from 4.3V to 3.0V at the above-mentioned rate. Here, 1C means that if the battery is charged at this current value for 1 hour, the current value will just be fully charged (100% charged). And, as an indicator of the fast charging characteristics, the charging capacity ratio is calculated in the form of the ratio of the charging capacity at 3.5C to the charging capacity at 0.1C. The results are shown in Table 1 below. In addition, after the charge and discharge test is completed, the precipitation position of lithium metal in the evaluation battery cell is visually observed. The results are combined and shown in Table 1 below.

[0123] [Table 1]

[0124]

[0125] From the results shown in Table 1, it can be seen that by setting the intensity ratio R(I G / I D ) is 7 or more carbon particle layers, thereby significantly improving the 3.5C / 0.1C charge capacity ratio. This shows that according to the present invention, in a lithium precipitation type lithium secondary battery, a rate characteristic that can cope with rapid charging can be exhibited.

[0126] In addition, it can be seen from Comparative Example 1, Example 2 and Example 3 that the charge capacity ratio can be significantly improved by using carbon particles having a higher strength ratio R as the material constituting the carbon particle layer (for example, using graphene instead of graphite).

[0127] Furthermore, it can be seen from Comparative Example 1 and Example 4 that the charge capacity ratio can be further improved by using an electron conductive material as the ion conductive reaction suppression layer, as opposed to using an electron insulating material.

[0128] Description of Reference Numerals

[0129] 10a stacked secondary battery,

[0130] 11' negative electrode collector,

[0131] 11” positive electrode collector,

[0132] 13 negative electrode active material layer,

[0133] 15 positive electrode active material layer,

[0134] 17Solid electrolyte layer,

[0135] 18 graphene layers (carbon particle layers),

[0136] 19 single cell layers,

[0137] 20 insulation layer,

[0138] 21 Power generation element,

[0139] 22 carbon black layer (ion conductive reaction suppression layer),

[0140] 23 Magnesium layer (lithium precipitation energy reduction layer)

[0141] 25 negative electrode collector plate (negative electrode ear),

[0142] 27 positive electrode collector plate (positive electrode ear),

[0143] 29Laminating film.

Claims

1. A lithium secondary battery comprising a power generation element, wherein the power generation element comprises: A positive electrode having a positive electrode active material layer disposed on the surface of a positive electrode current collector, wherein the positive electrode active material layer contains a positive electrode active material capable of storing and releasing lithium ions; a negative electrode having a negative electrode current collector on which lithium metal is deposited during charging; and a solid electrolyte layer, which is interposed between the positive electrode and the negative electrode and contains a solid electrolyte, The negative electrode current collector has a carbon particle layer disposed on at least a portion of a region of a main surface opposite to the solid electrolyte layer where the positive electrode active material layer faces the negative electrode current collector, the carbon particle layer including a G band peak intensity (I G ) and D band peak intensity (I D ) is more intense than R(I G / I D ) is carbon particles of 7 or more.

2. The lithium secondary battery according to claim 1, wherein The carbon particle layer includes carbon particles having an intensity ratio R of 50 or more.

3. The lithium secondary battery according to claim 1 or 2, wherein: The carbon particles include graphene.

4. The lithium secondary battery according to claim 1 or 2, wherein: Among the carbon particles contained in the carbon particle layer, the ratio of particles having their major axes oriented in the plane direction of the carbon particle layer is 80% or more.

5. The lithium secondary battery according to claim 1 or 2, wherein: The surface roughness (maximum height; Rz) of the main surface of the carbon particle layer on the solid electrolyte layer side is 15 μm or less.

6. The lithium secondary battery according to claim 1 or 2, wherein: The peel strength between the carbon particle layer and the negative electrode current collector is 5 N / m or more.

7. The lithium secondary battery according to claim 1 or 2, wherein: The carbon particle layer is disposed on a portion of the surface of the negative electrode current collector.

8. The lithium secondary battery according to claim 1 or 2, wherein: In a plan view of the power generating element, an outer peripheral end of the carbon particle layer is located inside an outer peripheral end of the solid electrolyte layer.

9. The lithium secondary battery according to claim 1 or 2, wherein: The solid electrolyte layer is provided with an ion conductive reaction inhibition layer on at least a portion of the region where the positive electrode active material layer faces the negative electrode collector on the main surface facing the negative electrode collector. The ion conductive reaction inhibition layer has lithium ion conductivity and inhibits the reaction between the lithium metal and the solid electrolyte.

10. The lithium secondary battery according to claim 9, wherein: The ion-conductive reaction-inhibiting layer has electron conductivity.

11. The lithium secondary battery according to claim 9, wherein The ion-conductive reaction-inhibiting layer has electron-insulating properties.

12. The lithium secondary battery according to claim 9, wherein: The ion conductive reaction suppressing layer has a Young's modulus of 2 GPa or more.

13. The lithium secondary battery according to claim 9, wherein: The ion conductive reaction suppression layer further includes a lithium deposition energy reduction layer on at least a portion of a main surface facing the negative electrode current collector. The lithium deposition energy reduction layer includes a single substance of an element capable of alloying with lithium, or a compound or salt containing the element.